Bio-based adhesive as well as preparation method and application thereof
By using quaternary ammonium salt compounds and polyphenol compounds to prepare bio-based adhesives, the problems of insufficient energy consumption and solvent resistance in the prior art are solved, and bio-based adhesives with high bond strength, reusable and solvent resistance are achieved.
Patent Information
- Application Number
- CN202510122992.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-25
AI Technical Summary
During the preparation process, existing bio-based adhesives require irreversible chemical reactions under high temperature conditions, which consumes a lot of energy and may produce by-products that are unfavorable to the environment. At the same time, their solvent resistance is insufficient, and the adhesive is easily soluble in an organic solvent environment, resulting in a decrease in the strength of the adhesive.
A bio-based binder is prepared by mixing and heating the solvent by removing the solvent. This method simplifies the preparation process, reduces energy consumption, and improves solvent resistance of the adhesive.
The prepared bio-based adhesive has super strong bonding strength and excellent reusability. It can maintain a high bonding strength after long-term soaking of organic solvents, and the process is simple and environmentally friendly.
Smart Images

Figure CN119875581A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adhesive materials, and in particular relates to a bio-based adhesive and a preparation method and application thereof. Background Art
[0002] As an important and indispensable material, adhesives are widely used in daily life and industrial production, such as food packaging, electronics, aerospace, automotive industry, medical industry and other fields. However, modern industrial adhesives usually rely on petrochemical resources, and their disadvantages include complex synthesis process, toxicity and non-biodegradability, which has inspired researchers to obtain new high-performance bio-based adhesives from renewable and natural raw materials.
[0003] Recently, Nature reported a class of adhesives made from sustainable sources such as epoxidized soybean oil, natural organic acids and natural phenols, which provide a promising alternative to traditional epoxy adhesives. Although the adhesive system uses natural bio-based raw materials, its preparation process still requires irreversible chemical reactions under high temperature conditions, which not only consumes a lot of energy, but also may produce byproducts that are unfavorable to the environment.
[0004] CN118126678A discloses a high-strength bio-based adhesive and a preparation method thereof. The bio-based adhesive is prepared by the following steps: first, lignin and tannin are mixed and water is added, the pH value of the mixture is adjusted, and the mixture is reacted under a first temperature condition; secondly, a glyoxal solution is added, the mixture is reacted under a second temperature condition, and the reaction product is filtered after the reaction is completed to obtain a mixture of glyoxalated lignin and tannin; then, nanocellulose is added and stirred evenly at a certain speed to form an adhesive system containing nanocellulose; finally, hexylamine and starch are added to the adhesive system for curing treatment, and a high-strength bio-based adhesive is obtained after curing. The bio-based adhesive prepared by this technical solution has excellent bonding strength, but does not have recyclability.
[0005] CN117510886A discloses a bio-based supramolecular adhesive and its preparation method and application. The supramolecular adhesive grafts benzoic acid and phenylboric acid onto the epoxy soybean oil molecular chain through a ring-opening reaction, and then removes the solvent by heating, so that the phenylboric acid group is gradually dehydrated and cross-linked to form a boron oxygen six-ring structure, thereby obtaining a bio-based supramolecular adhesive. The bio-based supramolecular adhesive provided by this technical solution has high bonding strength, good water resistance, and can be recycled and reused. However, the adhesive does not have solvent resistance. When it is exposed to an organic solvent environment, the adhesive may dissolve, resulting in a decrease in adhesive strength.
[0006] Therefore, it is necessary to develop a bio-based adhesive that can be prepared by a simple method, is solvent-resistant, reusable, and has high bonding strength. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a bio-based adhesive and a preparation method and application thereof. The bio-based adhesive is prepared from quaternary ammonium salt compounds and polyphenol compounds as raw materials, and has the characteristics of solvent resistance, reusability, high bonding strength, etc.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a bio-based adhesive, wherein raw materials for preparing the bio-based adhesive include a quaternary ammonium salt compound and a polyphenol compound.
[0010] The bio-based adhesive prepared by using quaternary ammonium salt compounds and polyphenol compounds as raw materials has super strong bonding strength and excellent reusability, and after long-term immersion in organic solvents, it still maintains high bonding strength and has good organic solvent resistance.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, the mass ratio of the quaternary ammonium salt compound to the polyphenol compound is 1:(0.5-2), for example, it can be 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:1.75 or 1:2, etc.
[0013] Preferably, the quaternary ammonium salt compound has the following structure:
[0014]
[0015] Wherein, R1, R2, R3, and R4 are each independently selected from any one of a substituted or unsubstituted C1-C30 straight chain or branched aliphatic hydrocarbon group, a substituted or unsubstituted C3-C30 alicyclic hydrocarbon group, and a substituted or unsubstituted C6-C30 aromatic group; the substituted substituents include any one of an amide group, an ester group, a carboxyl group, a hydroxyl group, or an alkoxy group, or a combination of at least two of them.
[0016] Among them, X - Selected from halogen anions or acid radicals.
[0017] Preferably, the quaternary ammonium salt compound includes any one of DL-carnitine hydrochloride, betaine hydrochloride, choline chloride or tetraethylammonium chloride, or a combination of at least two thereof.
[0018] Preferably, the polyphenol compound is a compound having the following structure:
[0019]
[0020] Wherein, the R1-R5 are each independently selected from hydrogen or hydroxyl, R2 is selected from any one of amino, hydroxyl, carboxyl, hydrogen, halogen or C1-C70 organic groups; and the R1-R5 include at least two hydroxyl groups.
[0021] Preferably, the polyphenol compound comprises any one of tannic acid, epigallocatechin gallate or pyrogallic acid, or a combination of at least two thereof.
[0022] In a second aspect, the present invention provides a method for preparing the bio-based adhesive as described in the first aspect, the preparation method comprising the following steps: mixing a quaternary ammonium salt compound, a polyphenol compound and a solvent, and heating to remove the solvent to obtain the bio-based adhesive.
[0023] Preferably, the solvent includes any one of water, methanol or ethanol, or a combination of at least two of them.
[0024] Preferably, the heating temperature is 60-100°C (for example, 60°C, 70°C, 80°C, 90°C or 100°C, etc.), and the heating time is 2-10h (for example, 2h, 4h, 6h, 8h or 10h, etc.).
[0025] In a third aspect, the present invention provides an adhesive material, wherein the adhesive material comprises the bio-based adhesive as described in the first aspect.
[0026] Compared with the prior art, the present invention has at least the following beneficial effects:
[0027] (1) The present invention prepares a bio-based adhesive by mixing a quaternary ammonium salt compound and a polyphenol compound, adding a solvent to dissolve the mixture, and heating to remove the solvent. The preparation process is simple and environmentally friendly. The bio-based adhesive has super strong bonding strength and excellent reusability to various materials, and after long-term immersion in organic solvents, it still maintains a high bonding strength and has good organic solvent resistance.
[0028] (2) The bio-based adhesive prepared by the preferred technical solution of the present invention has a bonding strength of up to 8.15 MPa to glass, 8.11 MPa to stainless steel, and 14.41 MPa to ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 FTIR spectrum of the bio-based adhesive provided in Example 1;
[0030] Figure 2 The bio-based adhesive provided in Example 1 1 H NMR spectrum;
[0031] Figure 3 The effect diagram of the stainless steel sample bonded with the bio-based adhesive provided in Example 1 after being immersed in different solvents for 14 days;
[0032] Figure 4 Schematic diagram of the process of bonding a substrate with the bio-based adhesive provided in Example 1 and a schematic diagram of the reaction principle. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0034] The sources of raw materials used in the following examples and comparative examples are as follows:
[0035] 1. Tannic acid: CAS No. 1401-55-4, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0036] 2. Epigallocatechin gallate: CAS No. 989-51-5, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0037] 3. Pyrogallic acid: CAS No. 87-66-1, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0038] 4. DL-Carnitine hydrochloride: CAS No. 461-05-2, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0039] 5. Betaine hydrochloride: CAS No. 590-46-5, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0040] 6. Choline chloride: CAS No. 67-48-1, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0041] 7. Tetraethylammonium chloride: CAS No. 56-34-8, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0042] Example 1
[0043] A bio-based adhesive, the preparation method of the bio-based adhesive comprising the following steps: 2g of DL-carnitine hydrochloride and 2g of tannic acid are mixed, 2mL of water is added to fully dissolve them, the mixture is heated at 100°C for 8h to remove water, and the mixture is cooled to 25°C to obtain the bio-based adhesive.
[0044] Example 2
[0045] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, the added amount of DL-carnitine hydrochloride is 1 g, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0046] Example 3
[0047] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, the added amount of DL-carnitine hydrochloride is 1.5 g, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0048] Example 4
[0049] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, the added amount of DL-carnitine hydrochloride is 3 g, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0050] Example 5
[0051] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, the added amount of DL-carnitine hydrochloride is 4 g, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0052] Example 6
[0053] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, an equal amount of DL-carnitine hydrochloride is replaced by betaine hydrochloride, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0054] Example 7
[0055] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, an equal amount of DL-carnitine hydrochloride is replaced by choline chloride, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0056] Example 8
[0057] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, an equal amount of DL-carnitine hydrochloride is replaced by tetraethylammonium chloride, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0058] Example 9
[0059] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, an equal amount of tannic acid is replaced by epigallocatechin gallate, and other raw materials, dosages and preparation methods are the same as those in Example 1.
[0060] Example 10
[0061] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, an equal amount of tannic acid is replaced by pyrogallic acid, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0062] Embodiment 11
[0063] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, the added amount of DL-carnitine hydrochloride is 5 g, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0064] Example 12
[0065] A bio-based adhesive, which differs from Example 1 in that, in the preparation of the bio-based adhesive, the amount of tannic acid added is 5 g, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0066] Comparative Example 1
[0067] A bio-based adhesive prepared according to the technical solution of Example 3 of CN118126678A.
[0068] Comparative Example 2
[0069] A bio-based adhesive prepared according to the technical solution of Example 1 of CN117510886A.
[0070] Test Method
[0071] 1) Bio-based adhesive bonding strength test, the test method is as follows:
[0072] The bio-based adhesive was heated to 100°C, and a sample with a material size of 100mm×25mm was taken. The substrate of the sample included any one of ceramic, glass, and stainless steel. 100mg of adhesive was applied between the two sample strips, and then bonding was performed at 100°C. The bonding area was 25mm×12.5mm, and the pressure was 1000Pa for 10 minutes. The bonding strength test was performed using a universal tensile testing machine. During the tensile test, the tensile rate was 5mm / min. The test was completed when the two materials were completely separated. The test was performed 3 times in total, and the average value was taken.
[0073] 2) Test of resistance of bio-based adhesive to organic solvents. The test method is as follows.
[0074] The bio-based adhesive was heated to 100°C, and a stainless steel sample with a material size of 100mm×25mm was taken. 100mg of adhesive was applied between the two sample strips, and then bonding was performed at 100°C with a bonding area of 25mm×12.5mm and a pressure of 1000Pa for 10 minutes. After being soaked in an organic solvent for 14 days, the bonding strength was tested using a universal tensile testing machine. During the tensile test, the tensile rate was 5mm / min, and the two pieces of material were stretched until they were completely separated as a complete test. A total of 3 tests were performed and the average value was taken.
[0075] 3) Test on reusability of bio-based adhesives. The test method is as follows.
[0076] Heat the bio-based adhesive to 100°C, take a sample with a material size of 100mm×25mm, the substrate of the sample includes any one of ceramic, glass, and stainless steel, apply 100mg of adhesive between the two sample strips, and then bond at 100°C, the bonding area is 25mm×12.5mm, and the pressure is 1000Pa for 10min. Use a universal tensile testing machine to test the bonding strength. During the tensile test, the tensile rate is 5mm / min. The test is completed when the two materials are completely separated. A total of 3 tests are conducted and the average value is taken. The above operation process is repeated 5 times and the average value is taken.
[0077] Test Results
[0078] The bio-based adhesives provided in Examples 1-12 were tested for bonding strength and reusability according to the above test methods. The test results are shown in Table 1:
[0079] Table 1
[0080]
[0081]
[0082] The bio-based adhesives provided in Examples 1-12 were tested for resistance to organic solvents according to the above test method. The test results are shown in Table 2:
[0083] Table 2
[0084]
[0085]
[0086] The bio-based adhesive provided in Example 1 was tested for reusability according to the above test method. The test results are shown in Table 3:
[0087] Table 3
[0088]
[0089] The test results of the bio-based adhesive provided in Comparative Examples 1-2 are shown in Table 4:
[0090] Table 4
[0091]
[0092] The test results show that:
[0093] (1) It can be seen from Examples 1 to 10 that the bio-based adhesive prepared by the present invention has super strong bonding strength to various materials, with a bonding strength of 0.41-8.15 MPa to glass, 0.35-8.11 MPa to stainless steel, and 0.45-14.41 MPa to ceramics. It has excellent reusability, with no significant decrease in bonding strength after being reused 5 times. It also has excellent resistance to organic solvents, and can maintain a relatively high bonding strength after long-term immersion in organic solvents.
[0094] (2) It can be seen from Examples 1 to 12 that the present invention can achieve a better technical effect of bonding strength by further optimizing the types and ratios of the polyphenol compound and the quaternary ammonium salt compound.
[0095] (3) It can be seen from Example 1 and Comparative Examples 1-2 that, compared with the bio-based adhesives provided in the prior art, the bio-based adhesive prepared in the present invention has more excellent material bonding strength, repeatability and solvent resistance.
[0096] Figure 1 This is the FTIR spectrum of the bio-based adhesive synthesized in Example 1. It can be seen from the figure that the bio-based adhesive prepared in Example 1 has the corresponding carbonyl and hydroxyl absorption peaks in the infrared spectra of DL-carnitine hydrochloride and tannic acid hydrogen spectrum, which confirms that the bio-based adhesive contains carbonyl and hydroxyl groups.
[0097] Figure 2 The bio-based adhesive synthesized in Example 1 1 H NMR spectrum. It can be seen from the figure that the bio-based adhesive prepared in Example 1 has the corresponding characteristic peaks in the hydrogen spectrum of DL-carnitine hydrochloride and tannic acid, which further confirms the structure of the bio-based adhesive.
[0098] Figure 3 This is a diagram showing the effect of the bio-based adhesive synthesized in Example 1 bonding the stainless steel sample after being immersed in different solvents for 14 days. It can be seen from the figure that the bio-based adhesive provided by the present invention did not separate from the substrate in the solvent after being immersed in different solvents for 14 days, which confirms that the bio-based adhesive provided by the present invention has excellent solvent resistance.
[0099] Figure 4 Schematic diagram of the process of bonding a substrate with the bio-based adhesive provided in Example 1 and a schematic diagram of the reaction principle.
[0100] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A bio-based adhesive, characterized in that: The raw materials for preparing the bio-based adhesive include quaternary ammonium salt compounds and polyphenol compounds.
2. The bio-based adhesive according to claim 1, characterized in that The mass ratio of the quaternary ammonium salt compound to the polyphenol compound is 1:(0.5-2).
3. The bio-based adhesive according to claim 1 or 2, characterized in that The quaternary ammonium salt compound is a compound having the following structure: Wherein, R1, R2, R3, and R4 are each independently selected from any one of substituted or unsubstituted C1-C30 straight-chain or branched aliphatic hydrocarbon groups, substituted or unsubstituted C3-C30 alicyclic hydrocarbon groups, and substituted or unsubstituted C6-C30 aromatic groups; the substituted substituents include any one of amide groups, ester groups, carboxyl groups, hydroxyl groups, or alkoxy groups, or a combination of at least two of them; Among them, X - Selected from halogen anions or acid radicals.
4. The bio-based adhesive according to any one of claims 1 to 3, characterized in that: The quaternary ammonium salt compound includes any one of DL-carnitine hydrochloride, betaine hydrochloride, choline chloride or tetraethylammonium chloride, or a combination of at least two thereof.
5. The bio-based adhesive according to any one of claims 1 to 4, characterized in that The polyphenol compound is a compound having the following structure: Wherein, the R1-R5 are each independently selected from hydrogen or hydroxyl, R2 is selected from any one of amino, hydroxyl, carboxyl, hydrogen, halogen or C1-C70 organic groups; and the R1-R5 include at least two hydroxyl groups.
6. The bio-based adhesive according to any one of claims 1 to 5, characterized in that The polyphenolic compound includes any one of tannic acid, epigallocatechin gallate or pyrogallic acid or a combination of at least two thereof.
7. A method for preparing a bio-based adhesive according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: mixing a quaternary ammonium salt compound, a polyphenol compound and a solvent, and heating to remove the solvent to obtain the bio-based adhesive.
8. The method for preparing the bio-based adhesive according to claim 7, characterized in that: The solvent includes any one of water, methanol or ethanol, or a combination of at least two of them.
9. The method for preparing the bio-based adhesive according to claim 7, characterized in that: The heating temperature is 60-100° C., and the heating time is 2-10 hours.
10. An adhesive material, characterized in that The adhesive material comprises the bio-based adhesive according to any one of claims 1-6.
Citation Information
Patent Citations
Induration process for powdered iron oxide containing material
CA590465A
Bio-based supramolecular adhesive as well as preparation method and application thereof
CN117510886A
High-strength bio-based adhesive and preparation method thereof
CN118126678A